Rupture mechanics of blood clot fibrin fibers A coarse-grained model study - Gu, Beikang (Journal of the mechanics and physics of solids, 2025)
Thrombosis, when occurring undesirably, disrupts normal blood flow and poses significant medical challenges. As the skeleton of blood clots, fibrin fibers play a vital role in the formation and fragmentation of blood clots. Thus, studying the deformation and fracture characteristics of fibrin fiber networks is the key factor to solve a series of health problems caused by thrombosis. This study employs a coarse-grained model of fibrin fibers to investigate the rupture dynamics of fibrin fiber networks. We propose a new method for generating biomimetic fibrin fiber networks to simulate their spatial geometry in blood clots. We examine the mechanical characteristics and rupture behaviors of fibrin fiber networks under various conditions, including fiber junction density, fiber tortuosity, fiber strength, and the strain limit of single fiber rupture in both tension and simple shear cases. Our findings indicate that the stress-strain relationship of the fibrin fiber network follows a similar pattern to that of individual fibers, characterized by a shortened entropy stretching phase and an extended transition phase. Fiber junction density, fiber strength, and single fiber rupture limit predominantly influence the stress of the network, while fiber tortuosity governs the strain behavior. The availability of more fibers in shear cases to bear the load results in delayed rupture compared to tension cases. With consideration of different factors of fibrin fibers in networks, this work provides a more realistic description of the mechanical deformation process in fibrin fiber networks, offering new insights into their rupture and failure mechanisms. These findings could inspire novel approaches and methodologies for understanding the fracture of fibrin networks during a surgical thrombectomy